2000
DOI: 10.1086/317315
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Runaway Stars

Abstract: Milli-arcsecond astrometry provided by Hipparcos and by radio observations makes it possible to retrace the orbits of some of the nearest runaway stars and pulsars to determine their site of origin. The orbits of the runaways AE Aurigae and µ Columbae and of the eccentric binary ι Orionis intersect each other ∼2.5 Myr ago in the nascent Trapezium cluster, confirming that these runaways were formed in a binary-binary encounter. The path of the runaway star ζ Ophiuchi intersects that of the nearby pulsar PSR J19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(182 citation statements)
references
References 17 publications
(13 reference statements)
4
175
0
3
Order By: Relevance
“…Limongi & Chieffi 2006;Woosley & Heger 2007) (see summary in appendix of Diehl et al 2006a), formally consistent with our derived 26 Al mass. The most massive star in Upper Sco was presumably a ∼50 M O5-O6 star, which may have exploded as a supernova about 1.5 Myr ago; the pulsar PSR J1932+1059 may be its compact remnant (Hoogerwerf et al 2000;Chatterjee et al 2004). But because of uncertainty of this event and no obvious supernova activity being evident in Sco-Cen less than 1 My ago (which would be seen e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Limongi & Chieffi 2006;Woosley & Heger 2007) (see summary in appendix of Diehl et al 2006a), formally consistent with our derived 26 Al mass. The most massive star in Upper Sco was presumably a ∼50 M O5-O6 star, which may have exploded as a supernova about 1.5 Myr ago; the pulsar PSR J1932+1059 may be its compact remnant (Hoogerwerf et al 2000;Chatterjee et al 2004). But because of uncertainty of this event and no obvious supernova activity being evident in Sco-Cen less than 1 My ago (which would be seen e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For each object, a selection of spectra centered on He i λ5876 is shown. The spectra are described in Table A.1. a binary system at an earlier stage in its evolution; in particular, (Hoogerwerf et al 2000; see also van Rensbergen et al 1996) argue that ζ Oph resulted from a supernova kick. Regardless of the evolutionary and dynamical history of this star, it did not reach the level of enrichment seen in ON stars.…”
Section: Binarity and The On Phenomenonmentioning
confidence: 99%
“…Recent studies (e.g., Palladino et al 2014) have shown that low-mass F or G stars can also travel with extremely high velocities, often exceeding the local Galactic escape velocity. Thus, stars in a cluster or a binary system can be kicked out by a perturbation of the system, for instance, such as in a threebody encounter or a supernova explosion (e.g., Hoogerwerf et al 2000;Perets 2009;Irrgang et al 2010;Zhang et al 2013). To be more specific, there are several possible formation scenarios for HVSs: (1) interaction of single stars with a central massive black hole (MBH); (2) tidal break-up of binary stars in the vicinity of a MBH; (3) three-body interactions involving single-star encounters with a binary or cluster of MBHs; (4) double detonation of SN Ia with a close system of a rapidly orbiting low-mass compact He star and a massive (∼1−1.2 M ) CO-white dwarf (Geier et al 2015); (5) single-degenerate SN type Ia consisting of a white dwarf and a main-sequence star (Liu et al 2013); (6) binary star disruption in dense interacting regions such as globular clusters or the Galactic bulge or disk; or (7) tidal disruption of dwarf galaxies in the Galaxy (Li et al 2015, and references therein).…”
Section: High-velocity Starsmentioning
confidence: 99%